2006
DOI: 10.1128/jcm.44.5.1863-1866.2006
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Epidemiological Assessment of Shiga Toxin-Producing Escherichia coli O84 Isolates from New Zealand

Abstract: Shiga toxin-producing Escherichia coli O84 isolates (n ‫؍‬ 22) were examined using culture-and molecularly based methods in order to compare their phenotypic and genotypic characteristics. These analyses directly linked Shiga toxin-producing Escherichia coli O84 isolates from cattle and sheep with human isolates indicating that New Zealand livestock may be a reservoir of infection.The first recorded case in New Zealand of Shiga toxinproducing Escherichia coli (STEC) O157:H7 was in 1993 (3), and since then, STE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…Most of the bacterial strains used in this study have been described elsewhere (3,11,12,13). Of the strains examined for ehxA, 215 were positive for stx only (99 for stx 1 only, 33 for stx 1 and stx 2 , and 83 for stx 2 only) and 141 were eae positive (115 were positive for eae only, 25 were stx 1 and eae positive, and 1 was stx 2 and eae positive).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the bacterial strains used in this study have been described elsewhere (3,11,12,13). Of the strains examined for ehxA, 215 were positive for stx only (99 for stx 1 only, 33 for stx 1 and stx 2 , and 83 for stx 2 only) and 141 were eae positive (115 were positive for eae only, 25 were stx 1 and eae positive, and 1 was stx 2 and eae positive).…”
Section: Methodsmentioning
confidence: 99%
“…The ehxA gene was more commonly associated with those strains that were eae positive (86.2%) than with those that were stx positive only (51.8%). Previously, ehxA has been used as a marker for identifying specific eae-and ehxApositive STEC serotypes such as O26, O103, O111, O145, and O157, which are more commonly associated with outbreaks of serious human clinical disease, including bloody diarrhea and HUS, than other serotypes (3,5,13,31,32,33,45,46). Indeed, all the eae-positive STEC strains examined in this study (n ϭ 38) were also ehxA positive.…”
Section: Vol 73 2007 Analysis Of Enterohemolysin Gene From Stec Andmentioning
confidence: 99%
See 1 more Smart Citation
“…A prevalence of 0.7% was reported for E. coli O157: H7 for sheep and lambs at slaughter in the UK (Milnes et al 2008), while an Irish study failed to detect any E. coli O157: H7 in the faeces of lambs at slaughter (Lenahan et al 2007). Information on STEC in lambs in NZ is limited, with no E. coli O157: H7 isolated in a survey of sheep (Cookson et al 2006). Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Since E. coli O157: H7 was first documented in NZ in 1993 (Baker et al 1999), numerous cases have been reported in clinical isolates and environmental sources, but the incidence in livestock appears to be low. Cookson et al (2006) examined faecal swabs from 46 lambs, but failed to identify any that contained both a Shiga toxin gene (stx1 or stx2) and the E. coli attaching and effacing gene, eae. In the USA, a study targeting E. coli O157 in lambs at slaughter showed a similarly low level of detection of 1.1% (McCluskey et al 1999).…”
mentioning
confidence: 99%